IMPLEMENTASI SURAT EDARAN MENTERI NO. 4 TAHUN 2020 TENTANG PENYELENGGARAAN PENDIDIKAN PADA MASA COVID DI SD NEGERI BERTINGKAT PERUMNAS 1 WAENA, JAYAPURA - Herry Polontoh; Silvester M.L. Palit (JURNAL PENGABDIAN PAPUA, 2022)
This service was carried out with the title of Implementation of Science and Technology Of The Minister's Circular Letter No. 4 of 2020 concerning the Implementation of Education during the Covid Period. The activity was carried out to partners in Perumnas 1 Waena State Elementary School, due to the constraints of teachers who have not understood the implementation of learning that can be done in accordance with government directives through The Minister's Circular Letter No. 4 of 2020 concerning the Implementation of Policies and Education in the Emergency Period of Corona Virus Disease Spread (Covid 19). Through this circular, learning methods in the covid-19 pandemic can be done online to minimize crowds or physical distancing efforts, which so far the team of servicemen meets learning methods are still done offline (face-to-face) because some teachers have not mastered online learning applications so that with the expertise possessed the serviceman can do the application of science and technology. The implementation of this devotion is carried out by the presentation of government discretionary materials through the implementation arrangements of distance education, discussions, and technical guidance in the operation of online learning methods, namely using the Zoom application, Whatsapp, Google Classroom, Google Meet, Google Drive and several other supporting applications by paying attention to the covid-19 protocol and assistance to partners in implementing online learning methods. The externality of this devotion is the increasing knowledge of partners about the implementation of learning in accordance with the Circular Letter of Minister No. 4 of 2020 in terms of learning using online methods in the covid-19 pandemic period, to break the chain of the spread of covid-19. Keywords: circular; covid-19 pandemic; online learning